Testing Purchasing Power Parity in Cambodia: Time-Varying Trade Weights in Constructing Real Effective Exchange Rate - Lim, Siphat (International Journal of Economics and Financial Issues, 2021)
The purchasing power parity (PPP) is generally accepted as the exchange rate projection between two countries relative to their inflation rate. However, despites many researches in the past years, the answer to whether the PPP holds, remains an on-going debate. The prior researches are criticized for their heavy reliance on the bilateral exchange rate which consists of short time-series or uses multilateral or real effective exchange rate (REER) constructed by the fixed trade weight. Finally, the implementing of only the most popular unit-root or stationary tests such as ADF and PP deems to diagnose with certain weaknesses, for instance, size distortion ascending from the heteroscedasticity. The main purpose of this study, therefore, is to study whether the PPP holds in Cambodia? In this paper, an alternative stationary test known as the KPSS test is incorporated with the stationary test thereof. Avoiding the aforementioned problem, the time-varying trade weights of Cambodia from 1995 to 2019 is employed to construct the total data points or months of 295 REER from January 1995 to July 2019 instead. The result indicates that the PPP theory holds in Cambodia based on the result generated by the ADF test modeled with constant and trend. The test result thereof also indicates that the REER of Cambodia has a mean reverting process. Keywords: Purchasing Power Parity, Real Effective Exchange Rate, Time-Varying Trade Weights, Unit Root Test JEL Classifications: F31, F41, C23 DOI: https://doi.org/10.32479/ijefi.10543